Molecular characterization of α-enolase and endonuclease A in Streptococcus pneumoniae towards the molecular interaction in netosis - Ahmad Zubaidi, A.latif; Mohd Adzim Khalili, Rohin; Mohd Khairi, Zahri@Johari; Nordin, Simbak (2018)
Streptococcus pneumonia is a causative agent for pneumococcal disease and a public concern due to high rate of mortality and morbidity reported each year. This Gram-positive bacteria can transmit from one person to another via inhalation and colonise at nasopharyngeal. Molecular characterization of genes of S. pneumonia is crucial in order to study the properties of virulent factor against human defense mechanism. This study aimed to analyse the sequence of α-enolase and endonuclease A genes of S. pneumoniae towards interaction in netosis. Netosis is one of the host defense mechanisms produced by neutrophils to kill any foreign antigens through a set of molecular proteins. In this study, the molecular characterization of these genes was performed and the associated elements were related with the netosis. Thus, the mechanism of interaction between proteins encoded by both genes with netosis will be further studied towards the development of S. pneumoniae vaccine candidates